PANDANGAN HUKUM PIDANA TERHADAP KASUS POLITIK UANG DALAM PEMILU TAHUN 2024: Criminal Law Views on Money Politics Cases in the 2024 Election - Pratama, Adrian; Arif Fadhlurrahman; Angga Arniya Putra; Tegar Gala Samudra; Willy Syain Islami; Yon Efri (PUAN INDONESIA, 2023)
Political corruption is a prominent phenomenon in modern politics, influencing political processes in various countries, including Indonesia. This article delves into the evolution of politics in Indonesia post-reform, with a focus on the role of political parties and the practice of money politics in elections. The main discussion explores the phenomenon of money politics, highlighting its correlation with political corruption and the role of political parties in society. Additionally, the article examines factors influencing the practice of money politics, such as the lack of closeness between political parties and the public, individual education levels, and low welfare standards. This analysis provides deep insights into the dynamics of money politics.By summarizing findings and implications from the analysis, this article suggests that money politics poses a serious challenge to the integrity of democracy and political justice. Therefore, efforts to prevent money politics should be a priority in strengthening a cleaner, fairer, and more transparent political system. Thus, this article makes a significant contribution to understanding money politics and efforts to address it for the sake of a healthy and sustainable democracy.